TEACHING LEARNING PROCESS OF A SYNTAX CLASS AT KRESNA ENGLISH LANGUANGE INSTITUTE PARE KEDIRI - Santoso, Didik (Jurnal Pendidikan Bahasa Inggris Proficiency, 2020)
The study is aimed to describe the teaching learning process of Syntax Class at Kresna English Language Institute. Those are including of:The teaching learning process, the English teacher’s problem, the problem solving of teacher, the student’s response, and the appropriate material for student.This research design used descriptive qualitative. The subjects were a teacher and 25 students of Syntax Class. The methods were observation, interview, and documentation. Observation used for collecting data on the teaching learning process that consisted of: lesson plan, the material, method, and media that the teachers used in teaching. Interview used for collecting data on the teachers’ preparation, students’ response, and the teachers’ evaluation in teaching learning process. Documentation was used to collect data about a record of events that have passed. This research had some results: (1the teaching learning process was running well by some phases such as : preparation, implementation and evaluation, (2) the problems of the teacher happened in implementation and in evalution phases,(3) in implementation, the problem faced by some advices and even punishment to the student and in evaluation the problem solved by giving motivation and additional duty,(4) there were more positive responses than negative responses from the students, ( 5 ) the appropriate material in this class was Syntactic stucture and sentence analysis. Theconclusion of this reseach was that the teaching learning process ran well, but there were some activities of teacher that were not suitable with lesson plan.